Rights, Knowledge Regimes and Indigenous Arts at universities and schools: essential entries, and some challenges - Horacio, Heiberle Hirsgberg; das Dores Fernandes Vitor, Maria; Leite Silva Xakriabá, Vanginei (Educação, Escola & Sociedade, 2022)
The article aims to highlight the indispensability of the entry and permanence of Indigenous Peoples, of their Knowledge and Arts Regimes at the University and brazilian schools, including for the transformation of this University and the schools. This article also seeks to highlight the importance of the Brazilian University being an ally in the fight for the Rights of Indigenous Peoples, and schools being a space for combating stereotypes and discrimination against Indigenous Peoples. Namely, this article built a “dialogue” between an indigenous master and artist who is a postgraduate student at a public university - the indigenous Nei Leite Xakriabá - with professor Joana Aparecida Fernandes Silva - who works in the area of ​​Indigenous Teacher Training, - bringing an important speech by Nei Xakriabá linked to the interview conducted by Joana Fernandes, as well as the considerations of the authors and the author of the article.